The impact of plyometric exercises on the physical fitness of amateur boxers in Jordan - Al-Shbul M.A.; Myasnikova T.I.; Vorobyev S.T. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to assessment of the impact of plyometric exercises on the explosive power of amateur boxers in Jordan. Methodology and organization of research. A study was carried out to evaluate the effectiveness of a training regimen employing the plyometric technique on the explosive power of 40 amateur boxers from Jordan. Results and conclusions. The findings of the pedagogical experiment demonstrate that the boxers' impact force improved by 25% over a two-month period, their impact velocity increased by 12%, and their explosive strength in their arms and legs improved by 18% and 15%, respectively. These results suggest that plyometric training can positively impact a range of indicators related to explosive strength in boxers. Therefore, it is essential to incorporate plyometric training into athletes' training programs to enhance their performance and achieve superior athletic outcomes.